Initial Studies on Temperature Impact of Humic Acid - Pashalidis, Ioannis; Kolokassidou, Konstantina; Costa, Costas; Efstathiou, Angelos M.; Buckau, Gunnar (My University, 2004)
The impact of temperature on the stability of the hiirnic acid Gohy-573(HA) is studied. The studies are made both in order to add general knowledge about humic acid but also in order to provide the basis for experimental setup of studies, and judgment of published data, on the metal ion humate complexation as a function of temperature. Methods applied are mass spectroscopy as a function of temperature elevation up to 240 °C. and UV/Vis spectroscopy. Mass spectroscopy is conducted under inertgas atmosphere in order to avoid burning with air oxygen. UV/Vis spectra are measured after storage of humic acid solution (pH=6.0, 1=0.1 MNaClO4) at temperatures up to 95 °C. The reversibility of changes is also studied by UV/Vis spectroscopy after subsequent storage at room temperature. Already at 50 °C release of water is observed from dried humic acid with a peak around 60°C. A second large water release is found with the maximum around 100 °C. Above 100 °C also carbon dioxide is released, followed by release of carbon monoxide above 130 °C. The carbon monoxide and dioxide releases show two distinct maxima at around 180 and 210 °C. The UV/Vis spectra show an increase in the absorption towards short wavelengths with increasing temperature and storage time. Already at 60 °C. considerable changes occur after storage for one week. At 95 °C the change in the spectral feature after 24 h is in the order of that found for 1 wreek storage at 80 °C. After storage at elevated temperatures, the changes in the spectra remain even after 1 week of storage at room temperature. Release of water, carbon monoxide and carbon dioxide at high temperature is certainly related to oxidation with the high oxygen inventory in humic acid. The nature of the water release and changes in the UV/Vis spectra at lower temperature is not fully clear. Further experiments, including complexation properties, fluorescence spectroscopy and IR-reflection spectroscopy at elevated temperature are under consideration.
Keywords: Temperature; Humic acid